Evaluating the Impact of Blockchain Technology on Sports Economics: A Psychological Perspective on Financial Management (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
The integration of blockchain technology is often associated primarily with Bitcoin; however, its applications extend far beyond. This paper proposes a novel approach utilising blockchain within sports organizations to enhance financial transparency and efficiency. By designing a distributed database system maintained by multiple independent nodes, each node retains a complete blockchain, ensuring data integrity and system stability even under potential cyber threats. In a hypothetical scenario where sports franchises utilize blockchain for transactional processes, such as trading media rights or sponsorships, the technology secures transactions and potentially influences market dynamics and pricing strategies. The application of blockchain could redefine how financial operations are managed in sports, enhancing both strategic decision-making and financial outcomes.